Innovative Human Management Practices in Colombia's Corporations: The Risaralda Sugar Mill Case (2019)
This article emphasizes technological change as an engine of structural changepromoting product development and new industries. Thus, innovation becomes thesource of economic growth in the long term and the explanation for thetransformation for the productive structure. To prove this point, the article presentsthe case analysis of the Risaralda sugar mill.